Concentration in Banking and Its Effect on Business Loan Rates - Edwards, Franklin R. (The Review of Economics and Statistics, 1964)
N recent years, we have seen a renewed interest in the problem of competition among banks. An increasing number of bank mergers has brought forth new legislation, such as the Bank Holding Company Act (1956) and the Bank Merger Act (1960), which directs regulatory agencies to preserve competition in banking. At the same time, it has become apparent that there is little or no empirical evidence on the relationship between bank performance and market structure. This paper aims chiefly at determining whether or not market structure or concentration has any effect on commercial bank performance. It is considered to be the groundwork from which it is hoped will spring more sophisticated techniques for handling the conceptual difficulties here encountered. It seems reasonable to begin an analysis of bank competition with what is undoubtedly the most delimited borrower market, the market for small business loans. There are fewer borrower alternatives for small business loans than for almost all other bank services. Business loans are also, of course, the most important component of commercial banks' loan portfolios. An investigation of this market provides an estimate of the upper bound of departures from competitive conditions. If no evidence of market power can be found in markets for business loans, other bank services for which there are more substitutes are not likely to display monopolistic practices. This paper attempts to test two hypotheses: (1) that, ceteris paribus, the level of business loan rates is higher in markets having relatively high concentration; and (2) that, ceteris paribus, business loan rates are less flexible in markets having relatively high concentration. In testing these hypotheses, an attempt is made to distinguish the effect of market structure from other regional differences, such as those of loan demand, bank costs, type of banking, etc. This paper seeks to probe the following questions: (1) What is a competitive market structure? (2) What is the quantitative effect of a given change in concentration, such as might result from a bank merger? (3) What determines the spatial market for bank loans? (4) Does branch banking have an effect on market performance different from that of unit banking? (5) How should market structure be measured? (6) Do banks which possess market power behave differently than competitive banks over the business cycle?